The perspectives of fresh-cut fruits and vegetables on the Zagreb market - Levaj, Branka (Array, 2020)
The fresh-cut fruits and vegetables (FCFV) are defined as products that have been trimmed and/or peeled and/or cut into 100% usable product that is bagged or pre-packaged to offer consumers a high nutrition, convenience and flavor while still maintaining its freshness. Fruits and vegetables (FV) are abundant with phytochemicals that indicate beneficial influence on human health when consumed frequently and as a part of daily diet. Healthy conscious consumers appreciate convenience of FCFV, but due to its extreme perishability sometimes their quality and safety may be questionable leading to its shortened shelf-life. Optimal processing as well as distribution conditions are imperative for prolonging their shelf-life. Hence, the prototype of vending machine (VM) for FCFV which could replace usual salad bars in food services and maintaining the highest hygiene criteria was constructed by funding of the BICRO-project and implemented at Faculty of Food Technology and Biotechnology University of Zagreb. In the first part of this study, performance of VM prototype in the cold storage of fresh-cut (FC) apple during 7 days was investigated and interest for FCFV by oral survey with Zagreb citizens was examined in the second part. Quality and sensory characteristics of FC apples stored in VM remained satisfactory for 4 days and microbial analysis showed that VM could provide a safe product for 7 days. Furthermore, the need for such device confirmed the tendency of consumers to choose their own FCFV combinations and purchase such products near the workplace. In general, market analysis proved increased consumers demand for FCFV.